A study on market entry strategy and cultural Influence on the marketing mix in Kenya: a case of Square Pharmaceuticals Ltd. - Chowdhury, Azmain Faek (BRAC University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2023.